Academic Achievement Assessment Principles and Methodology - Tian, Huisheng (Springer Berlin Heidelberg, 2018)
This book consists of introduction to academic achievement assessment, international comparison of academic achievement assessment and reference, as well as theoretical system and practice strategy of academic achievement assessment. The study indicates that the development trends of foreign academic achievement assessment are: establishing a complete education quality monitoring system; paying more attention to the function and value of independent education quality monitoring institution and intermediary organization; the orientation based on the integrated development of students growing more apparent; marching from "evaluation of study" to "evaluation for study"; and placing educational equity in a prominent position. This book is easy to understand and readable for professionals like teachers, educational researchers and particularly those engaged in academic achievement.